Attitude Towards Anti-smoking Measures and Its Associated Factors Among Adults in Sub-urban Area, in Kuala Terengganu, Terengganu, Malaysia - Oo, San San; Aung, Myat Moe Thwe; Ibrahim, Mohd Salami; Naing, Nyi Nyi; Mat Azmi, Intan Suhana Munira; Abd Aziz, Aniza; Aung, San Thitsa (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: General population across different countries have shown an overall support for anti-smoking measures that vary significantly by certain population parameters. However, characteristics of the public attitude in a community who has been exposed to prolonged awareness campaigns and smoke-free area legislation is unclear. Consequently, we investigate residents who reside next to Batu Buruk beach in Kuala Terengganu city which has been gazetted as a smoke-free area since 2017. Methods: The cross-sectional study involves self-administered validated questionnaires. Multiple linear regression with forward method was applied to identify significant factors associated with the attitude towards anti-smoking measures. Results: A total of 295 residents participated. Most of them were Malays (96.6%), married (64.4%), attained up to the secondary school level (45.4%) and employed (59.7%). The mean value of the total attitude scores was 181.86 (range: 70-200). Multivariate analyses revealed those having higher monthly income had a higher total attitude scores (adjusted b: 6.91, 95% CI: 2.15, 11.66), while current daily smokers had a lower total attitude scores towards anti-smoking measures than non-smokers (adjusted b: -23.30, 95% CI: -29.55, -17.05). These findings highlight comparatively stronger and more consistent support for anti-smoking measures that may vindicate high-stake investment and legislation against smoking. Conclusion: The novel evidence may also better-inform the strategy to expand the initiatives further through profiling the target population with heightened emphasis on the economic standing and prevalence of current daily smokers. Future research may adopt experimental design to establish causality relationship between predictors and outcomes revealed in this community.